Estimating the impact of expanding treatment coverage and allocation strategies for chronic hepatitis C in a direct antiviral agent era - Poovorawan, K; Pan-ngum, W; White, L; Soonthornworasiri, N; Wilairatana, P; Wasitthankasem, R; Tangkijvanich, P; Poovorawan, Y (Public Library of Science, 2016)
Hepatitis C virus (HCV) infection is an important worldwide public health problem, and most of the global HCV burden is in low- to middle-income countries. This study aimed to estimate the future burden of chronic hepatitis C (CHC) and the impact of public health policies using novel antiviral agents in Thailand. A mathematical model of CHC transmission dynamics was constructed to examine the disease burden over the next 20 years using different treatment strategies. We compared and evaluated the current treatment (PEGylated interferon and ribavirin) with new treatments using novel direct-acting antiviral agents among various treatment policies. Thailand’s CHC prevalence was estimated to decrease 1.09%–0.19% in 2015–2035. Expanding treatment coverage (i.e., a five-fold increment in treatment accessibility) was estimated to decrease cumulative deaths (33,007 deaths avoided, 25.5% reduction) from CHC-related decompensated cirrhosis and hepatocellular carcinoma (HCC). The yearly incidence of HCC-associated HCV was estimated to decrease from 2,305 to 1,877 cases yearly with expanding treatment coverage. A generalized treatment scenario (i.e., an equal proportional distribution of available treatment to individuals at all disease stages according to the number of cases at each stage) was predicted to further reduce death from HCC (9,170 deaths avoided, 11.3% reduction) and the annual incidence of HCC (i.e., a further decrease from 1,877 to 1,168 cases yearly, 37.7% reduction), but cumulative deaths were predicted to increase (by 3,626 deaths, 3.7% increase). Based on the extensive coverage scenario and the generalized treatment scenario, we estimated near-zero death from decompensated cirrhosis in 2031. In conclusion, CHC-related morbidity and mortality in Thailand are estimated to decrease dramatically over the next 20 years. Treatment coverage and allocation strategies are important factors that affect the future burden of CHC in resource-limited countries like Thailand.